Characterization of bacterial consortia from diesel-contaminated Antarctic soils: Towards the design of tailored formulas for bioaugmentation - Vazquez, Susana Claudia (2013)
In Antarctica, the environmental conditions and the restrictions imposed by the Antarctic Treaty prevent inoculation with foreign bacteria. Therefore, our aim was to investigate native bacterial consortia which might serve to design bacterial formulas suitable for soil bioremediation processes at cold temperatures. Two bacterial consortia, M10 and J13, were isolated from diesel contaminated Antarctic soils. Their ability to use hydrocarbons was evaluated in vitro and by the detection of three catabolic genes (alkB, nahAc, xylE). Both consortia showed similar 16S rRNA gene profiles, suggesting the presence of the same phylotypes. Total 16S rDNA was cloned from M10 grown on diesel. Sixty clones were screened, grouped by restriction profiles of PCR-amplified inserts and sequenced. T-RFLP (Terminal-Restriction-Fragment-Length-Polymorphism) of clones showed that all phylotypes from the entire consortia were recovered. A culture-dependent approach was used to isolate M10 components able to utilise aliphatic and aromatic hydrocarbons. Pseudomonas, Stenotrophomonas, Pedobacter and Brevundimonas genera were detected. The combination of dependent and independent culture methods allowed elucidating the taxonomic composition of these native bacterial consortia. Further work will assess whether combining the isolates obtained as a defined mixed culture can enhance bioremediation of contaminated soils.